Preferential peroneal nerve injury after acetabular fracture and reconstruction. Issue 2 (March 2018) - Goyal, Kanu S.; Hill, Michael; O'Malley, Michael; Mehta, Manish; Moossy, John; Tarkin, Ivan
Abstract : Background: Sciatic nerve dysfunction typically involving the peroneal division infamously plagues acetabular reconstruction through a posterior exposure. Competing explanations include mechanical compression from retractor placement at the hip versus overstretch. In an effort to improve the current care paradigm, we asked what underlying mechanisms of injury lead to preferential injury to the peroneal division of the sciatic nerve. Methods: A cadaver model was established to measure both sciatic nerve strain and intraneural pressure generated during simulated retraction performed during acetabular reconstruction. The tibial and peroneal divisions were studied independently using a micro differential variable reluctance transducer (DVRT) to quantify strain and an angiocatheter to measure intraneural pressure. Measurements were recorded at both the hip and knee. Results: Both divisions of the sciatic nerve experienced significantly more pressure at the hip than at the knee. Knee flexion reduced intraneural pressure of the peroneal division at the hip by approximately 30%. Intraneural pressure at the knee was significantly greater in the peroneal versus tibial nerve during knee extension, yet was reduced with knee flexion. Conclusions: Our results suggest that direct compression of the peroneal nerve during hip retraction has the most potential to cause iatrogenic sciatic nerve injury. Knee flexion was beneficial for decreasing nerve stretch and pressure. The peroneal division, however, is vulnerable to dysfunction because of the higher intraneural pressures experienced by the tethering effect of the fibular tunnel at the knee.